Bioenergy and CO₂ sequestration: Climate policies beyond technological constraints - Ruben Bibas; Aurélie Méjean (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper examines the role of electricity production from biomass with and without carbon capture and storage in sustaining low CO2 emission pathways to 2100. It quantifies the effect of the availability of biomass resources and technologies within a general equilibrium framework. Biomass-fed integrated gasification combined cycle technology is introduced into the electricity module of IMACLIM-R, a hybrid general equilibrium model. We assess the robustness of this technology, with and without carbon capture and storage, as a way of reaching the 550 ppm stabilization target. The impact of a uniform CO2 tax on energy prices and world GDP is examined, together with the structure of the electricity mix. The influence of additional climate mitigation policies, such as alternative recycling of tax revenues and infrastructure policies is also discussed.
Keywords: C68; F0; H23; Q01; Q4; Q5; 330; General Equilibrium Model; Macro-Economic Cost; Low Emission Objective; Electricity From Biomass; Carbon Capture and Storage; Negative Emissions; Elektrizitätsversorgung; Klimaschutz; Bioenergie; Kohlenstoffsenke; Energieprognose